Hypocalcaemia as A Predisposing Factor for Pregnancy Induced Hypertension (Journal of Fatima Jinnah Medical University, 2018)
Objective: To show correlation between serum calcium and development of pregnancy induced hypertensionDesign: Case control comparative study.Place & Duration of Study: This study was carried out in the Department of Obstetrics and Gynaecology unit II sir Ganga Ram Hospital, Lahore between January and December 2010.Patients and Methods: In this study 200 pregnant women attending antenatal clinic of Sir Ganga Ram Hospital were included. They were divided in two groups each having 100 women. Selection of each group was done through convenience, non-probability sampling technique. All women had at least one antenatal visit at or just before 20 weeks of pregnancy and had normal blood pressure till that time. Women presenting with prolonged hyperemesis, repeated gastro-intestinal upsets and twin pregnancy were excluded from the study. These women were followed in antenatal clinic till 30 weeks of pregnancy. Then two groups were made. Group I included 100 pregnant women with normal blood pressure with gestational age between 30-40 wks. Group II included 100 pregnant women, inclusion criteria was patients having diastolic blood pressure ≥ 100mmHg, with or without proteinuria and patients with or without convulsions having same gestational age range as that of group I. Detailed history especially dietary history was taken through a specially designed performa. Serum calcium levels were estimated in both groups.Results: Analysis of results showed that PIH developed in young patients who belonged to poor socioeconomic group & were not taking calcium regularly in diet and as calcium supplement and their total serum calcium level was significantly low. In group II 30% patient were taking regular dietary and supplementary calcium as compared to 60% patients in group I. Analysis of serum calcium level showed that average calcium level (7.36mg/dl) in group II ( patients with PIH) was significantly lower as compared to group I controls (8.5mg/dl).Conclusion: Study concluded that hypocalcaemia has a strong association with PIH and it is directly related to dietary and supplementary calcium intake.